Tingkat pemangsaan Neoseiulus longispinosus Evans (Acari : Phytoseiidae) terhadap Tetranychus urticae Koch dan Tetranychus kanzawai Kishida (Acari: Tetranychidae) serta perilaku kanibalismenya - Edwin Iswella; Pudjianto Pudjianto; Sugeng Santoso (Jurnal Entomologi Indonesia, 2016)
Tetranychus urticae Koch and Tetranycus kanzawai Kishida are important pests of various crops of economically importance in Indonesia.  Acaricide are commonly used to control these mites. One of the alternative control methods is the use of phytoseiid predatory mites. Most of the phytoseiid mites that are used as biological control agents are exotic mites. For that reasons, it is necessary to study indegenous predatory mites that has the potential to be developed as biological control, such as N. longispinosus. The objective of this study was to determine the predation capacities of N. longispinosus on two red spider mites of T. urticae and T. kanzawai and the effect of predator densities to predator cannibalistic behavior. N. longispinosus were supplied with eggs and adults of T. urticae and T. kanzawai to determine the predation capacities. N. longispinosus were also supplied low number of T. kanzawai eggs as the prey at several predator densities to see its cannibalistic behavior. The results showed that the number of eggs of T. urticae dan T. kanzawai consumed by deutonymphs and adult females of N. longispinosus was higher than the adult female of T. urticae dan T. kanzawai. The number of eggs of T. urticae dan T. kanzawai consumed by adult female N. longispinosus was higher than by the deutonymphs. The number of eggs laid by adult females of N. longispinosus when feed on eggs of T. urticae and T. kanzawai was higher than those feed on adult female. Deutonymph and female adult stage of N. longispinosus showed cannibalistic behavior at several predator densities in low number of prey.